(untitled) (Physical Education, Health and Social Sciences, 2026)
Northern Pakistan, encompassing Gilgit-Baltistan and Khyber Pakhtunkhwa, hosts some of the world’s most iconic high-mountain landscapes, including five of the fourteen eight-thousanders and extensive glacial systems, making it a rapidly growing destination for adventure tourism (trekking, mountaineering, white-water rafting, and cultural immersion). Post-pandemic foreign tourist arrivals surged by over 115%, intensifying pressure on fragile ecosystems, water resources, waste management infrastructure, and local communities. This review examines the current state of sustainable adventure tourism development in the region, analyzing national and provincial policy frameworks (National Tourism Strategy 2020–2030, KITE project), environmental challenges (glacial recession, GLOF risks, solid waste accumulation, and water pollution), and socio-economic dynamics. Special attention is given to community engagement models, including the Aga Khan Development Network’s Town Management Societies (TMS), revenue-sharing mechanisms from heritage sites and mountaineering royalties, women’s empowerment initiatives (e.g., CIQAM project, Maizban homestays), and professionalization of local guides. The paper contrasts Pakistan’s predominantly government-led approach with Nepal’s community-centric Annapurna Conservation Area Project (ACAP), highlighting opportunities to strengthen local governance, introduce regenerative practices, improve climate-resilient infrastructure, and enforce stricter environmental standards. Findings underscore that long-term viability depends on shifting from volume-driven growth to inclusive, regenerative models that equitably distribute benefits, preserve cultural identity, protect ecological integrity, and build institutional trust among residents, government, and private stakeholders.